INGLIZ VA OʻZBEK TILLARIDA FE’L TURLARINING CHOGʻISHTIRMA TADQIQI - Komilova Sevinch (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article is devoted to a comparative typological study of verb types and their grammatical, morphological, and syntactic features in English and Uzbek. The research methods used include contrastive analysis, morphological and syntactic analysis, and a comparative typological approach. The results of the study have practical implications for linguistic research, translation, and foreign language teaching methods.